2022
DOI: 10.1093/pnasnexus/pgac298
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution cryo-EM structure of the junction region of the native cardiac thin filament in relaxed state

Abstract: Cardiac contraction depends on molecular interactions among sarcomeric proteins coordinated by the rising and falling intracellular Ca2+ levels. Cardiac thin filament (cTF) consists of two strands comprised of actin, tropomyosin (Tm), and equally spaced troponin (Tn) complexes forming regulatory units. Tn binds Ca2+ to move Tm strand away from myosin-binding sites on actin to enable actomyosin cross-bridges required for force generation. The Tn complex has three subunits – Ca2+-binding TnC, inhibitory TnI, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 81 publications
1
28
0
Order By: Relevance
“…Presently, the prevailing pathomechanism ascribed to thin-filament mutations (cardiac troponins and tropomyosin) associated with HCM involves the disruption of tropomyosin's ability to block myosin-binding sites on actin. [43][44][45] When this blockade is disrupted, myosinbinding sites become more accessible, thereby facilitating the formation of force-producing crossbridges. 36 In HCM, the destabilization of tropomyosin's blockade of actin can be further facilitated by the reduced phosphorylation of myofilament proteins, such as cTnI (cardiac troponin I), by PKA (protein kinase A).…”
Section: Influence Of Thin-filament Hcm-causing Mutations On Actin-ta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, the prevailing pathomechanism ascribed to thin-filament mutations (cardiac troponins and tropomyosin) associated with HCM involves the disruption of tropomyosin's ability to block myosin-binding sites on actin. [43][44][45] When this blockade is disrupted, myosinbinding sites become more accessible, thereby facilitating the formation of force-producing crossbridges. 36 In HCM, the destabilization of tropomyosin's blockade of actin can be further facilitated by the reduced phosphorylation of myofilament proteins, such as cTnI (cardiac troponin I), by PKA (protein kinase A).…”
Section: Influence Of Thin-filament Hcm-causing Mutations On Actin-ta...mentioning
confidence: 99%
“…As Ca 2+ concentration rises, tropomyosin moves, exposing most of the actin’s myosin-binding sites. 45,46,52 However, myosin is relatively weakly bound to actin (in the myosin-ADP-Pi state), and the myofilament remains inactive. 53 Myofilament activation occurs with the formation of strongly bound force-producing crossbridges (in the myosin-ADP state).…”
Section: Adp’s Influence In Shifting the Equilibrium Toward The Drx S...mentioning
confidence: 99%
“…According to structural models of the F-actin-Tpm complex, only residues D20 and E181 form electrostatic contacts with a cluster of charged residues on actin comprising K326 and K328. 18,30 Results of this work provide mechanistic insights into the muscle disease phenotypes linked to mutations in TPM2. We found that, in consistency with the clinical phenotypes, mutations in first and second halves of the actin-binding periods of Tpm2.2 can either strengthen or weaken the inhibitory potential of Tpm2.2 by affecting the position of Tpm2.2 on the filament and changing kinetics of ATP turnover and product release by myosin head.…”
Section: Introductionmentioning
confidence: 99%
“…All four selected substitutions are in the “f” positions of the heptad repeat, which are exposed outside the coiled coil and are potentially available for Tpm2.2 interactions with binding partners (Figure 1B). According to structural models of the F‐actin‐Tpm complex, only residues D20 and E181 form electrostatic contacts with a cluster of charged residues on actin comprising K326 and K328 18,30 …”
Section: Introductionmentioning
confidence: 99%
“…1 A , green and yellow ribbons); ii) orienting the cTn core domain relative to the direction of the thin filament; and iii) stabilizing the tropomyosin head-to-tail region ( Fig. 1 A , black bracket) ( 3 10 ). Structural studies demonstrated that the loop region of TnT1 interacts with the actin backbone of the cardiac thin filament via ionic bonds ( Fig.…”
mentioning
confidence: 99%